Epiedafic invertebrate survey in lead contaminated environment (Research, Society and Development, 2020)
The objective of this work was to characterize the epiedaptic fauna in soil contaminated by lead in the Southwest region of Paraná. The work was carried out in the area of a deactivated battery recycler, which was subdivided into 6 blocks with direct influence of contamination and 2 blocks, as a reference, located outside the contamination perimeter. The edaphic fauna was sampled by installing 4 Pitfall-traps in each plot, which remained 6 days in the field, with subsequent classification of the sampled organisms. To determine the lead content, in each plot 4 soil samples were collected and homogenized for analysis in the laboratory. The plots with direct influence have lead values above what is allowed by the legislation and demonstrate differentiation in the composition of the epiedaphic fauna in relation to the control areas, presenting a greater wealth of groups, greater diversity and uniformity, and the presence of exclusive groups, such as Blattodea, Dermaptera, Gastropoda and Isopoda. The Formicidae family showed high abundance in the soil with a higher lead content, showing to be a good indicator of this condition. The Collembola class showed no development limitation in the contaminated areas, with a high abundance of the group being found in all the plots, especially in those where the vegetation is more developed.